Best Answer

From second equation: y = 8 + 2x

Substitute for y in first equation: 3x + 16 + 4x = 2

ie 7x = -14

ie x = -2 and y = 4

Q: Solve this equation using substitution 3x plus 2y equals 2 and -2 plus y equals 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

You'd need another equation to sub in

-2

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

Related questions

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

You'd need another equation to sub in

-2

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0

True

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

George saves nickels and dimes for tolls. If he has 8 coins worth $2.60,how many are nickels and how many are dimes? Answer this question by using system of equation.

G-Given U-Unknown E-Equation S-Substitution S-Solve

To solve a system of equations using substitution you solve one of the equations for one of the variables then substitute that into the other equation to solve for the other variable. For example. y = 6x 2x + 3y = -20 The first equation has already been solved for y. So, you simply substitute that into the second equation. 2x + 3(6x) = -20 2x + 18x = -20 20x = -20 x = -20/20 = -1 Now you have solved for x. You can substitute your answer for x back into the first equation to solve for y. y = 6x = 6(-1) = -6 Putting it all together... x = -1 y = -6

Mathematical substitution is the process of using one equation to solve for multiple variables. For example: Equation 1: x + y = 4 Equation 2: 2x + y = 16 Using equation 1, solve for y: y = 4 - x <-- Plug this into equation 2. This is substitution because you are replacing y in equation 2 with what y is equal to in equation 1. 2x + y = 16 ----> 2x + (4 - x) = 16 Now you can solve for x: x + 4 = 16; x = 12 You can then substitute the value of x back into the equation that is solved for y: y = 4 - 12; y = -8 Check both equations: Equation 1: -8 + 12 = 4; 4 = 4 (Correct) Equation 2: 2(12) + (-8) = 16; 24 - 8 = 16; 16 = 16 (Correct) We have successfully used substitution to solve for two different variables, x and y.